Phase-Fast Estimation Algorithm Using PLL and Feed-Forward - Kim, Kuk-Hyeon; Park, Jin-Wook; Park, Seong-Mi; Park, Sung-Jun (International Journal of Engineering and Technology, 2018)
Background/Objectives: In order to compensate the fluctuation of the generator frequency when the load of the generator suddenly changed, the control system by the mechanical time constant is operated through the governor control.Methods/Statistical analysis: In this paper, we propose an algorithm to detect the active power of the generator momentarily and to perform feedforward control using it to reduce frequency fluctuation when the load suddenly changed. A high - speed PLL algorithm for grid linkage by phase estimation is also proposed in the case of phase topologyFindings: In order to compensate the instability of the phase information obtained from the two-phase stationary coordinate system, the proposed high-speed PLL algorithm implements an algorithm for estimating the phase angle robust to the disturbance as a result of using the phase information on the stationary coordinate system using the low.Improvements/Applications: As a result of the use of the proposed algorithm through the PSIM simulation, a highly interlaced phase angle test was implemented and applied to the coupled inverter.Â